Spatial and temporal patterns of abundance of Aedes aegypti L. (Stegomyia aegypti) and Aedes albopictus (Skuse) [Stegomyia albopictus (Skuse)] in southern Florida. Issue 4 (27th December 2012) - REISKIND, M. H.; LOUNIBOS, L. P.
Abstract : Invasion by mosquito vectors of disease may impact the distribution of resident mosquitoes, resulting in novel patterns of vectors and concomitant risk for disease. One example of such an impact is the invasion by Aedes albopictus (Skuse) [ Stegomyia albopictus (Skuse)] (Diptera: Culicidae) of North America and this species' interaction with Aedes aegypti L. ( Stegomyia aegypti L). We hypothesized that Ae. aegypti would be found in urban, coastal areas that experience hotter and drier conditions, whereas Ae. albopictus would be more commonly found in suburban and rural areas that are cooler and wetter. In addition, we hypothesized that Ae. aegypti would be more abundant early in the wet season, whereas Ae. albopictus would be more abundant later in the wet season. Urban areas were drier, hotter and contained more Ae. aegypti than suburban or rural areas. Aedes aegypti was relatively more abundant early in the wet season, whereas Ae. albopictus was more abundant in both the late wet season and the dry season. The spatial patterns of inter‐ and intraspecific encounters between these species were also described. The distribution of these mosquitoes is correlated with abiotic conditions, and with temperature, humidity and the relative availability of rain‐filled containers. Understanding the ecological determinants of species distribution can provide insight into the biology of these vectors and important information for their appropriate control.